Modified initial era checklist for screening ergonomics risk factors in diagnosing work-related musculoskeletal disorders - Ibrahim Adham Taib,; Niza Samsuddin,; Noor Artika Hassan,; Norhanna Sohaimi,; Nor Azlina Abdul Rahman,; Zaitunnatakhin Zamli,; Dewililah Sapriah Yosof,; Muhamad Ariff Muhamad Noordin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Work-related musculoskeletal disorders (WRMSDs) are known to affect a diverse range of occupations around the world. One major factor for their occurrence is the presence of ergonomics risk factors in the workplace; as such, steps to minimise WRMSDs in Malaysia include the development of the Initial Ergonomics Risk Assessment (ERA) checklist for on-site assessors. The checklist, however, may not be useful for medical doctors who diagnose WRMSDs in hospitals or clinics. Moreover, there is no tool to assist medical doctors in considering the role of ergonomics risk factors when diagnosing WRMSDs, which can hamper the overall management of occupational diseases. This study was therefore carried out to modify the Initial ERA checklist so that medical doctors can use it to consider the role of ergonomics risk factors when diagnosing WRMSDs. In Phase I, document analysis was performed to construct the tool by integrating elements that were relevant for use in hospitals or clinics from the Initial ERA checklist and similar tools published overseas. In Phase II, the tool was reviewed by medical doctors and nurses and was found to have excellent content validity (I-CVI = 1.00). In Phase III, the tool underwent further improvement after trailing its application in two role-play sessions involving various healthcare professionals. The resulting Modified Initial ERA Checklist can assist medical doctors screen for various ergonomics risk factors when diagnosing WRMSDs in hospitals or clinics.